Evaluating the effect of foliar applied manganese, iron, zinc and boron at different growth stages of Mash bean [Vigna mungo (L.) Hepper] - Fatima, Hira; Tahir, Muhammad; Saleem, Muhammad Abdullah (Journal of Pure and Applied Agriculture, 2023)
Pulses cultivation in Pakistan has been markedly declined although these are highly nutritious. Micronutrients deficiency is increasing due to their fixation in calcareous soils of Pakistan. To overcome this problem, a field trial was carried during 2019 at University of Agriculture Faisalabad to assess the effectiveness of different micronutrients (Mn, Fe, Zn and B) on black gram. Randomized Complete Block Design (RCBD) with three replications was used. Chakwal mash was used as a test variety. The treatments were [Control, Water spray at 25 DAS (Days after sowing), Water spray at Flowering, Mn (0.5%) at 25 DAS, Mn (0.5%) at Flowering, Fe (0.5%) at 25 DAS, Fe (0.5%) at Flowering, Zn (0.5%) at 25 DAS, Zn (0.5%) at Flowering, B (0.5%) at 25 DAS, B (0.5%) at Flowering]. Growth parameters observed were significantly affected with treatment (T8) with foliar application of 0.5 % Zn at 25 DAS. Significantly, the maximum plant height (59.26 cm), number of pods per plant (17.00), pod length (4.63 cm), number of seeds per pod (8.66), 1000-grain weight (35.16 g), seed yield (1031.3 kg ha-1 ), biological yield (3366.7 kg ha-1 ), HI (30.63%), grain carbohydrate contents (60%), grain protein contents (23.00 %) were observed in mash bean when 0.5% foliar spray of Zn was applied at 25 DAS. The highest grain Mn, Fe, Zn and B concentration (0.20, 7.60, 3.40, 0.09 mg/100 g) were recorded when 0.5% foliar spray of respective micronutrient was applied. Boron spray also affected the parameters in a similar way with providing fruitful results which were at par with zinc. In conclusion, application of Zn at early stages while the application of B at lateral stages is equally important in yield escalation in mash bean. © 2021 Department of Agricultural Sciences, AIOU